Foraminifera Biostratigraphy and Paleobathymetry of the Ombilin Formation in the Sumpur Kudus Area, Sijunjung Regency, West Sumatra, Indonesia - Febi Annisa; Budhi Setiawan; Yogie Zulkurnia Rochmana (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2026)
The Ombilin Formation in the Sumpur Kudus area, Sijunjung Regency, West Sumatra, is known for its abundance of foraminiferal fossils. However, studies on the relative age of the rock layers, particularly regarding paleobathymetry, still require more in-depth research. This study aims to determine the relative age and bathymetric environment of the Ombilin Formation. The research method used is foraminiferal microfossil analysis, which includes identifying planktonic and benthic foraminifera from rock samples in the study area. The data used consist of five carbonate rock samples. The results of the study indicate that the relative age of the Ombilin Formation in the Sumpur Kudus area, Sijunjung Regency, West Sumatra, based on planktonic foraminifera analysis, is Early Miocene (N5), and its bathymetric environment, based on benthic foraminifera analysis, is in the neritic margin to mid-neritic zone (11–175 fathoms). Thus, the results of this study not only confirm previous findings but also strengthen evidence regarding the relative age and depositional characteristics of the Ombilin Formation, in both regional and local contexts, thereby providing supporting data to understand the geological history and evolution of sedimentation in the Ombilin Basin.